The analysis of type-2 fuzzy controller for ITER PF ac/dc converter control system. (August 2019) - Ul Hassan, Mahmood; Humayun, Muhammad; Huang, Liangsheng; Waheed, Bushra; Fu, Peng; Song, Zhiquan
Abstract: This novel type 2 fuzzy controller (T2FC) have more attractive research to developed the membership functions (MF) and rule uncertainties in the complex tokamak International Thermonuclear Experimental Reactor (ITER) Poloidal Field (PF) system. The uncertainties always happened to design the MF in real time applications. This paper proposes the T2FC design strategy in single and parallel operation. During the operations it is inflexible to handle the extremely uncertain and cannot determine the membership grades by conventional type 1 fuzzy controller (T1FC). To address the uncertainties issues the T2FC is the robust technique to accommodate the rule and membership uncertainties.